Effect of Workshop Training on Nursing Students’ Knowledge and Attitude Regarding Children’s Privacy Protection: A Quasi-experimental Study - Fatemeh Azimi; Fariba Asgari; Yasaman Yaghobi; Saman Maroufizadeh; Morteza Rahbar Taramsari (Journal of Holistic Nursing and Midwifery)
Introduction: Hospitalized children are exposed to privacy violations due to low knowledge of patient rights in healthcare providers especially nursing students. Training on how to respect the privacy of child patients by practical methods such as workshop training may affect the knowledge and attitude of nursing students. Objective: This study aimed to determine the effect of workshop training on the knowledge and attitude of children’s privacy protection in nursing students from Rasht, north of Iran. Materials and Methods: This quasi-experimental study was conducted in 2023 on 54 nursing students from the School of Nursing and Midwifery, Guilan University of Medical Sciences, Rasht, Iran. They were randomly allocated into two groups of control (n=28; received routine training) and intervention (n=26, received one-day workshop training). Their attitudes and Knowledge were assessed before and after training using researcher-made children’s privacy knowledge and attitude scales. Data analysis was performed by using descriptive (Mean±SD, frequency, percentage) and inferential statistics (Pearson correlation test and analysis of covariance). P<0.05 was considered statistically significant. Results: The mean age of the students was 22.62±1.53 years in the control group and 22.96±1.57 years in the intervention group. The majority of them were female (55.6%); 53.6% in the intervention group and 57.7% in the control group. Before the intervention, no significant difference was found between the two groups in the scores of attitudes and knowledge. After the intervention, the mean scores of attitude (P=0.001) and knowledge (P=0.001) significantly increased in two groups. The mean score of knowledge after training was significantly higher by 11.6 units in the intervention group than in the control group (F(1, 51)=13.77, 95% CI; 5.3%, 17.9%, P=0.001). The effect size was 0.213. The mean attitude score in the intervention group was significantly higher than in the control group by 7.1 units (F(1, 51)= 20.45, 95% CI; 3.9%, 10.2%, P=0.001) after training. The effect size was 0.286. Conclusion: One-day workshop training can improve the knowledge and attitude of nursing students regarding children’s privacy protection. It is recommended that nursing professors use workshop training to improve students’ knowledge and attitudes towards patient privacy.